Mixed fungal strains challenge host resistance: insights into Magnaporthiopsis maydis pathogenicity in maize - Shofman, Galia; Degani, Ofir (Frontiers in Microbiology, 2025)
Maize late wilt disease, caused by the fungus Magnaporthiopsis maydis, poses a significant threat to susceptible crops. Despite efforts to control it through resistant maize varieties, virulent fungal strains might overcome immunity. This study assessed Israeli M. maydis strains with weak, moderate, and highly pathogenic degrees in two open-air pot trials. Even weak pathogenic strains harmed susceptible cultivars (17% growth suppression and 33% death). In contrast, resistant cultivars were minimally affected, except when exposed to a highly aggressive isolate, resulting in a 5% growth suppression and 11% mortality at harvest. Unexpectedly, in a susceptible cultivar during sprouting, a mixed inoculum with the two more virulent isolates resulted in reduced disease (15%) compared to the highly aggressive strain alone (33%). At harvest (day 84), this pattern was reversed, and adding a weak virulent strain to this combination led to more severe growth (33%) and health (71%) disruption, accompanied by a higher level of M. maydis infection (371% compared to the aggressive strain alone). Similar interactions were found in other strain groups tested. Additionally, some subspecies groups specialize in growth suppression, while others in wilting, suggesting biotrophic/necrotrophic variations. The study revealed complex interactions in mixed populations, emphasizing the destructive potential of the pathogen to resistant cultivars. Understanding the role of maize age-related immunity in disease generation uncovers risks associated with this pathogen.